Depresi Pasca-Stroke: Diagnosis dan Tatalaksana - Ayu Susilawati; Ratep N; Kusuma Putera (Cermin Dunia Kedokteran, 2014)
Depresi pasca-stroke (PSD) merupakan salah satu komplikasi stroke dengan prevalensi 9-60%. Patofisiologi PSD yaitu: hipotesis lokasi lesi, ukuran infark, depresi vaskuler, faktor biokimia neuronal seperti hipotesis neurotransmiter, disfungsi imun, aktivasi aksis hipotalamik-pituitari-adrenal dan hipotesis neurogenesis. Diagnosis depresi berdasarkan DSM IV TR. Alat skrining diagnosis depresi yang digunakan adalah: Patient Health Questionnaire (PHQ) 2, PHQ 9, geriatric depression scale, hospital anxiety and depression scale, stroke aphasia depression quetionnnaire-10, aphasia depression rating scale, visual analog mood scale (VAMS). Penatalaksanaan PSD meliputi cara non farmakologi dan farmakologi.Post stroke depression (PSD) is one of stroke complications with prevalence of 9-60%. Theories of pathophysiology involved : the hypothesis of infarct location, infarct size, vascular depression, biochemical neuronal factor such as hypothesis of neurotransmitter, immune dysfunction, hypothalamic-pituitary-adrenal axis activation and neurogenesis hypothesis. Diagnosis is based on DSM IV TR using diagnostic screening tools. Screening diagnose of depression that is used: Patient Health Questionnaire (PHQ) 2, PHQ 9, geriatric depression scale, hospital anxiety and depression scale, stroke aphasia depression quetionnnaire-10, aphasia depression rating scale, visual analog mood scale (VAMS). Treatment consist of pharmacological and non-pharmacological methods.